PENEGAKAN HUKUM TERHADAP HAK ASUH ANAK AKIBAT PERCERAIAN DALAM PRAKTIK PERADILAN DI BALI - Ni Nyoman Sukerti (University of Udayana, 2015)
Our research aims to find and analyze the laws applied by judge to custody of children due to divorce related to the enactment of legal pluralism. Related to this, the issues raised in this research are: 1). What law applied by judges to child custody of divorce related to the enactment of legal pluralism? 2). What factors are the basis for consideration of the judge in determined custody of children divorce?. The results showed that the judge in determined custody of children of divorce apply national law. That is child to custody by mother may or paternal. Children who are under the care of the mother did not lose the right to inherit the father's side. The factors on which the consideration of the judge in determining child custody is a national marriage law, the cause of the divorce, and ensuring the interests the future of children, parenting by mothers did not abort child right inherit the father's side. The conclusion that the judge in determined the custody of children due to divorce apply national law. The factors on which the consideration of the judge in determining child custody is a national law, the cause of the divorce, and ensuring the interests of future child, parenting did not abort of child in her father's right to inherit.